A retrovirus carrying the polyomavirus middle T gene induces acute thrombocythemic myeloproliferative disease in mice. - Fusco, A (1988)
Mice inoculated with an artificially constructed retrovirus carrying the middle T gene of polyomavirus develop acute myeloproliferative disease with severe thrombotic and hemorrhagic disorder and impaired platelet function. The megakaryocytic lineage appears to be a target for polyoma-murine leukemia virus infection and middle T gene expression. This newly described disease represents a unique model system for studying disorders of the megakaryocytic lineage.